Strengthening Religious Character and Social Attitudes Through the Islamic Personal Development Program in Integrated Islamic Junior High Schools - Dini Sutanti; Khojir; Fathul Jannah (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of the Islamic Personal Development Program (Bina Pribadi Islam, BPI) in fostering students’ religious character and social attitudes in integrated Islamic junior high schools. The research addresses concerns over moral degradation among adolescents and the need for effective character education models grounded in Islamic values. A qualitative descriptive approach was employed, utilizing in-depth interviews, observations, and document analysis to collect data. Data were analyzed through condensation, display, and conclusion drawing to capture the program’s impact comprehensively. The findings indicate that BPI is implemented systematically through mentoring sessions (halaqah), habitual worship practices, and social activities. This approach effectively enhances students’ religious character, including discipline in worship, honesty, and responsibility, while also promoting social attitudes such as cooperation, tolerance, and empathy. Program effectiveness is influenced by mentor competence, student participation, and parental involvement. Key supporting factors include institutional commitment, a conducive religious environment, and teacher role modeling, whereas barriers involve limited time, lack of family integration, and an overemphasis on ritual over social development. The study concludes that BPI represents a holistic and effective Islamic character education model, yet its sustainability and impact can be strengthened through enhanced implementation, stakeholder collaboration, and integration of social development components.